Investigation of common risk factors between polycystic ovary syndrome and Alzheimer's disease: a narrative review - Nahid Sarahian; Hosna Sarvazad; Elham Sajadi; Nasrin Rahnejat; Narges Eskandari Roozbahani (BMC, 2021)
Plain English summary Polycystic ovary syndrome is a disorder of the female reproductive system that can be caused by hormonal disorders. The disease is detected by an ultrasound of the ovaries with small ovarian cysts. Obesity and insulin resistance are among the factors that can affect the clinical symptoms of this disease. Obesity due to high-fat consumption can affect cognitive functions with age. Alzheimer's is the most common disease associated with disorders in brain cells; a link between hormonal disorders and Alzheimer's has recently been reported. We conducted a review of reports and articles published in connection with polycystic ovary syndrome and neurodegenerative disorders in reputable scientific databases. Studies have shown that the factors involved in polycystic ovary syndrome and Alzheimer's disease may indicate that both diseases have common risk factors. It may be linked to the symptoms and/or complications of Alzheimer's disease and polycystic ovary syndrome. Future preclinical studies are needed to closely examine the mechanisms associated with polycystic ovary syndrome and the association with Alzheimer's. The novelty of our study is from the fact that the PCOS may be to some extent considered as a cause (exposure) among others of AD's (outcome) and the association might be confounded by some or all the risk factors assessed in this review. The nature of the method-the narrative review-is relatively subjective (in the determination of which studies to include, the way the studies are analyzed, and the conclusions drawn) and hence may not help mitigate bias.